The Monsoon Shock in Rural Nepal : Panel Evidence from the Household Risk and Vulnerability Survey - Jacoby, Hanan G. (World Bank, Washington, DC, 2019)
Monsoon rainfall is a key driver of economic life in rural Nepal as well as a major source of income variability. In this paper, the authors use a newly collected 3-year panel data set, representative of rural Nepal, merged with global monthly precipitation data to investigate the nature of the monsoon shock and to quantify household vulnerability to it. The authors find that the impact of the monsoon shock is concentrated in communities where water-intensive paddy dominates wet season cultivation and, coincidently, where groundwater irrigates dry season cultivation. In these communities, household size, area cultivated, agricultural and non-agricultural income, and household per capita food consumption measured nine months after the wet season harvest, all decline in response to a negative monsoon rainfall shock. A one standard deviation fall in monsoon precipitation is estimated to reduce total income by 3.8 percent and lead to a 0.8 percent drop in food consumption for the average rural household, but these figures rise to 11.5 percent and 3.3 percent, respectively, for households in the most paddy-intensive communities. These results have implications for social protection policies, especially in the lowlands of Nepal.